Medicine Users' Perspectives on Self-medication - Shrestha, Santosh (AMC Journal, 2023)
This paper provides an anthropological assessment on self-medication practices. It seeks to investigate representations associated with self-medication and identify contextual elements which can reinforce or inhibit such practice by employing medicine-users' perspective on the non-compliance of prescription. Primarily based on the informal conversations/interviews with 10 informants, it analyzes how socio-cultural and different forces shape our understanding of and actions towards health, illness and healing and the ways of wondering and behaving related to self-medication. It explores a few determinants for self-medication including the influence of medicine-sellers, circle of family members and friends, the role of pharmaceutical marketing, notion of the health problem as transitory and a minor issue, familiarity with and easy access to certain medicines, and difficulties in access to health care professionals. It concludes that the ubiquity of cultural practice of self-medication is the function of the concept of people on inaccessibility, time consumption, unaffordability and dissatisfaction in the delivery of formal health care services.